PEMBINAAN KARAKTER SISWA MELALUI BUDAYA LITERASI - Naelasari, Desy (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This study aims to describe the character of students, fostering student character through literacy culture at Pancasila Mojowarno Junior High School in Jombang. This research uses qualitative methods with descriptive qualitative research design. The data collection techniques used are interviews, observation, documentation. The data was analyzed by means of data reduction, data display, verification, and conclusion. Test the validity of the data in this study using extended observation, increasing persistence, triangulation. The results of this study are student characters at Pancasila Mojowarno Jombang Junior High School including: religious, honest, tolerance, responsibility. Student Character Development through Literacy Culture at SMPN 1 Mojowarno Jombang includes: mandatory library visits (fostering responsibility and religious characters), reading non-lesson books before learning begins (fostering creative, honest, and disciplined characters), holding literacy work competitions every semester (fostering creative, honest, and disciplined characters), creating mini libraries / literacy corners in the classroom (fostering responsibility characters).